PERANCANGAN WADUK MUNDINGAN DI KOTA SEMARANG - Abror, Muhammad Taufiq; Setiawan, Rizka; Darsono, Suseno; Nugroho, Hari (Jurnal Karya Teknik Sipil, 2015)
Flood in the Semarang City occur every year in the rainy season, drought and water shortages in the dry season. It has been built Jatibarang Reservoir and upstream there is a potential reservoir that could add to the raw water supply and flood control. The analysis used in planning reservoir that is the analysis of hydrology and hydraulics. Hydrological analysis using methods Soil Conservation Service Unit Hydrograph Synthetic (SCS) and Unit Hydrograph Synthetic of GAMA I. Q100 flood discharge plan with 165 mm of rain, the result of a method SCS unit hydrograph assisted HEC-HMS program amounting to 442 m3 / sec while the HSS GAMA I method with 218 mm of rain discharge plan generated at 359.02 m3 / sec. Flood discharge calculation used is a method SCS. PMF flood resulting from rainfall of 2408.7 mm deep as 677 m3 / sec. With the design of flushing water of 1.7 m3 / sec then storage volume up to 20,000,000 m3 and a storage volume of sediment up to 1,000,000 m3. With the reservoir can reduce flooding 100-year period by 77% from 442.9 m3 / sec to be 97.1 m3 / sec, and reduces the PMF discharge of 66% of 2408.7 m3 / sec to be 814.2 m3 / sec and reservoirs totaling 38 million m3. Dam 34 m high, dam crest 10 m wide, rock fill zone embankment type and spillway crest width of 20 m